Analisis Kesesuaian Karakteristik Lokasi Halte Busway Kota Semarang Berbasis Transit Oriented Development (Tod) - Kamila, Noor Annisa; Mulyanto, Budi; Hidayat, Janthy Trilusianthy (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
The implementation of the Bus Rapid Transit (BRT) System in Semarang City is an opportunity to create a spatial quality area for controlled mobility with the integration of the BRT System and land use activities using the concept of transit-oriented development (TOD) based area. The location of this research is within 800 meters radius of 16 start and final transit points in 8 corridors of BRT Trans Semarang. This research aims to determine the suitability of the characteristics of the application of the TOD Concept on BRT Trans Semarang. The variables used are building density, accessibility, connectivity, land use, and park and ride. The research method used is descriptive quantitative research by providing an assessment of each variable on the suitability of the existing conditions of each transit point. The result of this research indicates that the bus stop that has the highest percentage level of conformity of the TOD characteristics is the Tawang Station bus stop 87% and the lowest percentage level of conformity of the TOD characteristics is Ahmad Yani Airport Terminal bus stop 33%.